GMAT Prep Quant Missed : Quant Question Archive [LOCKED]
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 21 Jan 2017, 00:55

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# GMAT Prep Quant Missed

Author Message
Intern
Joined: 16 Aug 2006
Posts: 12
Followers: 0

Kudos [?]: 0 [0], given: 0

### Show Tags

20 Jan 2007, 12:20
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Hi All~~

Attached is a file of quant questions I missed on my first GMAT prep test. Can anyone out there help explain the answers to some of these? THANKS!!!!!

Attachments

gmatprep3_quantmissed_jan20.xls [698 KiB]

Intern
Joined: 14 Jan 2007
Posts: 19
Followers: 0

Kudos [?]: 0 [0], given: 0

### Show Tags

20 Jan 2007, 14:20
Why don't you just post them into the body of a message? The danger of downloading files from the internet will likely discourage people from answering.
SVP
Joined: 01 May 2006
Posts: 1797
Followers: 9

Kudos [?]: 149 [0], given: 0

### Show Tags

20 Jan 2007, 14:31
Q12) C

Arc / Perimeter = Angle / Total Angle

Implies,

24 / (D*Pi) = 240 / 360
<=> D*Pi = 36
<=> D = 36/(22/7) = 7*18/11 = 11,45 = 11
SVP
Joined: 01 May 2006
Posts: 1797
Followers: 9

Kudos [?]: 149 [0], given: 0

### Show Tags

20 Jan 2007, 14:38
Q18) E)

I) b @ a
= b + a - b*a
= a + b - a*b
= a @ b

II) a @ 0
= a + 0 - a*0
= a

III)
(a @ b) @ c
= (a + b - a*b) @ c
= (a + b - a*b) + c - (a + b - a*b)*c
= a + b + c - a*b - a*c - b*c + a*b*c (1)

a @ (b @ c)
= a @ (b + c - b*c)
= a + (b + c - b*c) - a*(b + c - b*c)
= a + b + c - b*c - a*b - a*c + a*b*c (2)

Thus (1) & (2) are equivalent
Intern
Joined: 16 Aug 2006
Posts: 12
Followers: 0

Kudos [?]: 0 [0], given: 0

### Show Tags

20 Jan 2007, 20:55
20 Jan 2007, 20:55
Display posts from previous: Sort by